Impact of Nutritional Intervention Using Mung Bean Juice and Soy Milk on Hemoglobin Levels in Adolescent Girls - Radiah, Radiah; Siregar, Sarinah; Lubis , Sunarti; Sulastri, Sulastri; Karwiti, Witi (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objectives: Anemia, which the general population is more familiar with as anemia, is below normal or is known as hemoglobin (HB), with women's typical levels being 11 gr/dl and 13 gr/dl in teenage boys. Anemia data in the Jambi Province area, the number of anemia sufferers aged 10-14 years (19.5%), 15-24 years (84.6%), 25-24 years (33.7%), 35-44 years (33 .6%), and 45-54 years (24%). Data on the number of anemia in Muaro Jambi is 97 people Methods: his study employed a quasi-experimental design methodology (quasi-experimental) pretest and posttest intervention to compare green bean juice and soy milk for 14 days. Results: One-way ANOVA was used to evaluate the data. The variables iron, folic acid, vitamin C in the green bean juice intervention obtained a p value of 0.000. The variables iron, folic acid, vitamin C in the soy milk intervention obtained a p value of 0.000. Showing that the hemoglobin levels between the intervention group, the control group of green bean juice and soy milk had quite large significant differences. As a result, hemoglobin levels in the soy milk intervention group in adolescents increased significantly compared to the green bean juice control group with a ratio of 0.68 g/dl per 500 ml to the average hemoglobin level before to the test administration of green bean juice. Conclusion: The conclusion obtained According to this study, young women's hemoglobin levels can rise when they are given green bean juice and soy milk.